Characterization of coorbit spaces with phase-space covers - Romero, J.L. (2012)
We show that coorbit spaces can be characterized in terms of arbitrary phase-space covers, which are families of phase-space multipliers associated with partitions of unity. This generalizes previously known results for time-frequency analysis to include time-scale decompositions. As a by-product, we extend the existing results for time-frequency analysis to an irregular setting. © 2011 Elsevier Inc.